Nokia's Shrinking Market Share in India: Can Nokia Sustain its First-Mover Advantage? - Shivakanth Shetty, A. (Indian Journal of Marketing, 2011)
Business in general, and stock markets in particular, have proven to be merciless punishers for the companies, who take their early success as granted and tend to be unimaginative and uncompetitive in the face of ever changing dynamics of business. Business history is full of such companies, who have fallen from grace and have become extinct like dinosaurs because of the comprehensive changes of technology, tastes and preferences, competitors and disruptive innovations. Nokia's shrinking market share in USA, China and India is nothing but an indicator to prove that all is not well within Nokia and it is all set to enter the long list of companies who have fallen from the grace of customers. Hence, this paper makes an attempt to probe the reasons for the dwindling global market share of Nokia in general and India in particular. This paper also evaluates Nokia's opportunities and strategic challenges to get back on track in the Indian Market by using Michael E Porter's Five Forces Model and Barney's "Firm Resources and Sustained Competitive Advantage" Model in India.